Chronic otitis media progressing to temporal bone osteomyelitis and sequestration with mastoid cavity myiasis in paediatric age group: an unusual case report - Basavaraj, Prashanth Kudure; Anandappa, Manjunatha H.; Sharma, Nishtha; Karkala, Shreyas; Prabhakaran, Veena (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Myiasis is the infestation by fly larvae. There are few sporadic publications regarding human ear myiasis. Osteomyelitis of temporal bone is also an uncommon entity. This study aims to describe the clinical presentation and management of a unique presentation of mastoid cavity myiasis and sequestration in a 4 year old child, who presented to Chigateri district hospital, Davangere with blood tinged discharge along with visible maggots from left external auditory canal and post auricular sinus since 3 days, with history of chronic otitis media. After manual cleaning of maggots, high resonance computed tomography of temporal bone was done, which showed findings suggestive of foreign body with bony density. Modified radical mastoidectomy was done, where osteomyelitis of temporal bone with sequestrum was encountered on table and removed. Diagnosis of temporal bone osteomyelitis requires a high degree of suspicion, especially in a setting of myiasis, as these 2 rare pathologies have not been reported to co-occur in literature. Early intervention is essential to avoid fatal complications of this infrequent presentation.